Application of electromagnetic waves as a solution to some agricultural problems - Ida Idayu, B.M.; Maryam Ashayer, S.; Amin, E.; Aliakbarian, H.; Ameri Mahabadi, H.; Mahmoud, M. (2010)
A review of some applications of electromagnetic waves in agriculture is presented. There are many applications in the literature which are categorized in two sections of post-harvest indoor and pre-harvest outdoor applications. Taking a look at the applications suggested, there are still works to be done to industrialize the method. However, the proposed method is promising in special cases when the cost and hazards of other methods are high.